Exploring Oxygenated Sesquiterpenes from Merauke Agarwood as PBP1a and PBP3 Inhibitors in Acinetobacter baumanii: An In-Silico Approach - Yulianto Ade Prasetya; Triono Bagus Saputro; Yohanes Ardian Kapri Negara; Arif Luqman (Jurnal Penelitian Pendidikan IPA, 2026)
Acinetobacter baumannii is a multidrug-resistant pathogen causing severe nosocomial infections, primarily associated with alterations in penicillin-binding proteins (PBPs) that reduce the effectiveness of β- lactam antibiotics. Despite increasing interest in plant-derived bioactive compounds, the potential of oxygenated sesquiterpenes from Aquilaria malaccensis as inhibitors of PBPs remains underexplored, indicating a clear research gap. This study aimed to evaluate the antibacterial potential of three oxygenated sesquiterpenes—Agaruspirol, Eudesmol, and Sinenofuranol—against PBP1a (3UE3) and PBP3 (3UDF). A systematic literature review (SLR) integrated with an in silico approach was conducted, including ligand retrieval from PubChem, ADMET prediction using ADMETlab 3.0, molecular docking using CB-Dock2, interaction analysis with UCSF ChimeraX and PLIP, and antibacterial activity prediction using PASS Online. The results showed that all compounds satisfied Lipinski’s rule of five and exhibited favorable ADMET profiles. Molecular docking demonstrated stable interactions with both PBPs, dominated by hydrogen bonding and hydrophobic interactions. Agaruspirol exhibited the strongest binding affinity toward PBP3 (–6.9 kcal/mol) and PBP1a (–6.5 kcal/mol), along with the highest predicted antibacterial activity (Pa = 0.364; Pi = 0.039). These findings suggest that oxygenated sesquiterpenes, particularly agaruspirol, have potential as lead compounds for the development of antibacterial agents targeting PBP-mediated resistance in A. baumannii, and provide a scientific basis for further in vitro and in vivo validation.